Komunikasi Antar Budaya Dalam Perspektif Antropologi Islam - Putri Ayuni; Anni Zuhro Syafrida Hasibuan; Suhairi Suhairi (STIT Sirojul Falah Bogor, 2022)
Intercultural communication develops based on two interconnected premises. First, you live in a time when changing technology, travel, economic and political systems, immigration patterns, and population density have resulted in a world in which you regularly interact with people from different cultures. Second, nowadays, people are very sensitive to the fact that the influence of culture on communication is very close and great. Your cultural background and experience help you determine how the world should be for you and how you will interact with it. Anthropological perspective in intercultural communication is looking at intercultural communication from an anthropological point of view, because the communication already contains cultural values. Intercultural communication is part of the marriage between the disciplines of anthropology and communication which later became a separate discipline both in communication science and in anthropology. Anthropology is one of the fields of science that is the root or foundation of the birth of communication science. In subsequent developments, cultural experts realized the importance of communication in the cultural field. Keywords: Intercultural communication and in anthropological perspective